CARA MENINGKATKAN KESADARAN PELANGGARAN HAK ASASI MANUSIA DI MEDIA SOSIAL: STUDI MENURUT ALKITAB - Dosmaria Panjaitan; Edom Sinaga; Damayanti Nababan (CV. Denasya Smart Publisher, 2024)
Millennial society does not recognize the existence of humnans towards other humanns. Human rights violations occur in various areas of life. The basic foundation of human rights comes from religious roots. Humans are the image of God and in Paul's language, human is divine original. The Bible places a very high place on human dignity which contains an understanding that reflects respect for the rights and freedoms of human life. This journal uses qualitative research methods, namely research/research whose sources are textbooks, journals and other written materials that are considered relevant. Based on research findings, it was found that technological developments also created new ways of human rights violations. To overcome this problem, governmnent of issued Law no. 11/2008 regarding Information and Electronic Transactions (ITE) which regulates human rights, this is because the existing laws are deemed insufficient to address human right cases/issues in this millennial era.